Fiction on the fringe : novelistic writing in the post-classical age - Karla, Grammatiki A. (Mnemosyne, Supplements, 2009)
This collection of essays offers a comprehensive examination of texts that traditionally have been excluded from the main corpus of the ancient Greek novel and confined to the margins of the genre, such as the Life of Aesop, the Life of Alexander the Great, and the Acts of the Christian Martyrs. Through comparison and contrast, intertextual analysis and close examination, the boundaries of the dichotomy between the "fringe" vs. the "canonical" or "erotic" novel are explored, and so the generic identity of the texts in each group is more clearly outlined. The collective outcome brings the "fringe" from the periphery of scholarly research to the centre of critical attention, and provides methodological tools for the exploration of other "fringe" texts.